How emotions shape memory? The moderating effect of healthy emotionality on eyewitness testimony - Glomb, Kaja; Piotrowski, Przemysław; Gulla, Bożena; Romanowska, Iza; Mastek, Maria (Frontiers in Psychology, 2024)
The influence of emotions on memory is a significant topic in the psychology of eyewitness testimony. However, conflicting results have arisen, possibly due to varying approaches and methodologies across studies. These discrepancies might also arise from inadequate consideration of individual differences in emotionality. Therefore, this study aims to analyze the moderating effect of healthy emotionality on the relationship between emotion and memory of criminal events. The results of our laboratory experiment (N = 150) conducted with VR technology indicate that eyewitnesses of crimes, unlike observers of neutral events, recall details concerning the perpetrators' actions immediately preceding the crime act better. Notably, individuals with lower scores on a scale measuring healthy emotionality (ESQ) demonstrate enhanced recollection for these details. At the same time, emotionality plays no significant role in recollection in repeated measurement, as well as in remembering the neutral event. The emotions experienced during crime observation appear to hinder the recollection of perpetrator appearance and behavior unrelated to the crime. These findings are discussed in light of the adaptive role of negative emotions in detecting danger and preparing for unpleasant stimuli.